2016
DOI: 10.1038/srep27805
|View full text |Cite
|
Sign up to set email alerts
|

Increased Thermal Conductivity in Metal-Organic Heat Carrier Nanofluids

Abstract: Metal-organic heat carriers (MOHCs) are recently developed nanofluids containing metal-organic framework (MOF) nanoparticles dispersed in various base fluids including refrigerants (R245Fa) and methanol. Here, we report the synthesis and characterization of MOHCs containing nanoMIL-101(Cr) and graphene oxide (GO) in an effort to improve the thermo-physical properties of various base fluids. MOHC/GO nanocomposites showed enhanced surface area, porosity, and nitrogen adsorption compared with the intrinsic nanoMI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…Experimental data of thermal conductivity measured at room temperature for various MOFs compared to some typical inorganic materials (shadowed area). [31,32,[34][35][36]51,[110][111][112][113][114][115][116] tremendous opportunities to optimize the electronic structure for high p-and n-type ZT values via deliberate choices of metals and ligands. Besides, their structural long-range crystalline order could facilitate charge carrier mobility to enhance σ without reducing S. Furthermore, their capability to host a large variety of guest molecules and nanostructures within their pores significantly distinguishes them from other nonporous organic materials, enabling the further tunability in electronic and thermal transport characteristics.…”
Section: Design Conductive Mofs For Thermoelectric Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data of thermal conductivity measured at room temperature for various MOFs compared to some typical inorganic materials (shadowed area). [31,32,[34][35][36]51,[110][111][112][113][114][115][116] tremendous opportunities to optimize the electronic structure for high p-and n-type ZT values via deliberate choices of metals and ligands. Besides, their structural long-range crystalline order could facilitate charge carrier mobility to enhance σ without reducing S. Furthermore, their capability to host a large variety of guest molecules and nanostructures within their pores significantly distinguishes them from other nonporous organic materials, enabling the further tunability in electronic and thermal transport characteristics.…”
Section: Design Conductive Mofs For Thermoelectric Applicationsmentioning
confidence: 99%
“…Recent studies demonstrated that materials in this class all exhibit thermal conductivities less than 0.4 W m −1 K −1 regardless of structure, composition, or morphology. [31][32][33][34][35][36] However, thermoelectric properties of MOFs have not yet been extensively investigated mainly because of the difficulty in achieving sufficiently high electrical conductivity. Generally, the connected rigid metal ions and redox-inactive organic ligands raise the energy barrier for electron transfer, making them electrical insulators.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have also reported improving nanofluid thermal conductivities with increasing temperature, and suggest increasing Brownian motions of the suspended nanoparticles as a possible mechanism 66 , 67 . Since increasing Brownian motions tends to promote micro-convection, which in turns enhances local mixing 68 , 69 .…”
Section: Resultsmentioning
confidence: 97%
“…MOF‐5 composites doped with 10 wt% of expanded natural graphite show a significant enhancement (≈460%) of the thermal conductivity . Nandasiri et al found that MIL‐101(Cr) and graphene oxide composite can induce a significant increase in the thermal conductivity (≈50%) respective to the intrinsic nano MIL‐101(Cr) . In a short summary, the studies of thermal conductivity of MOF adsorbents in breakthrough experiments remain to be explored in the future.…”
Section: Mofs In Co2 Capture Practicementioning
confidence: 99%